Quantum theory of many-variable systems and fields - Sakita, B (World Scientific, 1985)
Includes index; Bibliography: p. 209-210; These lecture notes are based on special courses on Field Theory and Statistical Mechanics given for graduate students at the City College of New York. It is an ideal text for a one-semester course on Quantum Field Theory.